ANTIGONE: Accurate Navigation Path Caching in Dynamic Road Networks leveraging Route APIs - Yu, Xiaojing; Li, Xiang-Yang; Zhao, Jing; Shen, Guobin; Freris, Nikolaos M.; Zhang, Lan (Annual Joint Conference of the IEEE Computer and Communications Societies, 2022)
Navigation paths and corresponding travel times play a key role in location-based services (LBS) of which large-scale navigation path caching constitutes a fundamental component. In view of the highly dynamic real-time traffic changes in road networks, the main challenge amounts to updating paths in the cache in a fashion that incurs minimal costs due to querying external map service providers and cache maintenance. In this paper, we propose a hybrid graph approach in which an LBS provider maintains a dynamic graph with edge weights representing travel times, and queries the external map server so as to ascertain high fidelity of the cached paths subject to stringent limitations on query costs. We further deploy our method in one of the biggest on-demand food delivery platforms and evaluate the performance against state-of-the-art methods. Our experimental results demonstrate the efficacy of our approach in terms of both substantial savings in the number of required queries and superior fidelity of the cached paths.